Genome scale transcriptional response diversity among ten ecotypes of Arabidopsis thaliana during heat stress - Barah, Pankaj; Jayavelu, Naresh D.; Mundy, John; Bones, Atle M. (Frontiers in Plant Science, 2013)
In the scenario of global warming and climate change, heat stress is a serious threat to crop production. Being sessile, plants cannot escape from heat and have developed various adaptive mechanisms to survive heat stress. Several studies have focused on diversity of heat tolerance levels in divergent Arabidopsis thaliana (A. thaliana) ecotypes, but comprehensive genome scale understanding of heat stress response in plants is still lacking. Here we report the genome scale transcript responses to heat stress of 10 A. thaliana ecotypes (Col, Ler, C24, Cvi, Kas1, An1, Sha, Kyo2, Eri and Kond) from different geographical locations,. A. thaliana plants were subjected to heat stress (38°C) and transcript responses were monitored using Arabidopsis NimbleGen ATH6 microarrays. The responses of Arabidopsis ecotypes exhibited considerable variation in global transcript levels. In total, 3644 transcripts were significantly heat regulated (p